Fecr suresi’nin eğitim açısından yorumu - Dolmacı, Ayşe (My University, 1999)
We decided on four main parts in our work. The relation of each part with the education is captured under the topics Facts about education seperately added. The subjects main idea, our reasoning and the methods we used are presented in the introduction part. The relation of Suretul Fecr with education is shown with the main basics. The Oath Matter topic includen the importance of oath giving, the meanings an oath can carry and the must of using brain power. Under the topic Social facts-historical examples; the reason of total amihilation punishment on the historical tribes of Ad, Semud and Firavun, with the commun exil alligned bases, is told; the importance of anectodes in the education is underlined, the education methods and principles of the prophets' that were gifted to those tribes are examined. After detailing Mankind's positive and negative sided psycological aspects carried from the creation and the relation of these aspects in the Sure, the Human Psycology part tries to materialize that these negative feelings, force the human to stay in mystical darkness. The same part, also, includes human, inheritance and orphan concepts. The motivating force of education with the stages of the Stand is told. And the material and spiritual losses probable to be suffered with a wroy choise of a loving concept are factisized. Nefs (The centre of desire) concept, human evolution fact, the importance of idolizing this fact to self and the dynamics that affect this evolution are caried out on The Evolution of Nefs The close relatiion ship between evolution and education are realized. Affects of gifts and punishments on a person's education motivation is detailed. As a result, human evolution is the world's most important subject. And for tun to occur education is needed. Education, in the first place, should motivate mankind in the search fortle perfect.
Keywords: Ayetler ve sureler (Kuran); Din; İslam Dini